2012
DOI: 10.1007/s00264-012-1708-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress fractures in elderly patients

Abstract: Purpose The purpose of this study was to investigate specific risk factors, common fracture locations and possible sexspecific differences in elderly patients with stress fractures. Methods This analysis enrolled 105 patients (83 women, 22 men) with stress fractures. For the analysis of possible risk factors related to increasing age, data from 82 patients (67 women, 15 men) aged 40 years and older (mean age of 57.4 ± 11.0 years) were compared with that from a younger control group [23 patients (16 women, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…17,22 One additional report of a positive relationship between calcium and vitamin D insufficiency and stress fractures exists, but refers to elderly patients with nonspecific, non-exercise-related stress fractures and is therefore of limited relevance. 21 The implications of our findings for men are unclear in light of the fact that despite consuming less calcium than uninjured controls, TSI injured men were still calcium replete; meeting or exceeding the daily recommended allowance.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…17,22 One additional report of a positive relationship between calcium and vitamin D insufficiency and stress fractures exists, but refers to elderly patients with nonspecific, non-exercise-related stress fractures and is therefore of limited relevance. 21 The implications of our findings for men are unclear in light of the fact that despite consuming less calcium than uninjured controls, TSI injured men were still calcium replete; meeting or exceeding the daily recommended allowance.…”
Section: Discussionmentioning
confidence: 81%
“…An association of reduced bone strength with incidence of TSI is intuitive, in light of the mechanostatic adaptive remodeling response of bone to chronic repetitive strain that exceeds the normal physiological threshold. 27 A number of previous studies have reported relationships between bone strength and bone stress injuries, 1,2,12,[14][15][16][17]21,22 supporting the notion that certain morphological features of bone, especially narrow width, predispose individuals to bone stress injury in general 9,11,15,16 and tibial stress injuries more specifically. 20 By contrast, we did not observe differences in BMD between groups, and BMD was normal for the whole cohort, despite previous reports of low BMD as an independent risk factor for stress fractures.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Considering international literature we found many works about stress fractures in athletes (especially in endurance athletes), instead we found a lower number of articles about stress fracture in elderly patients (5,6). Stress fractures result from an unsuccessful bone adaptation to mechanical changes induced by repetitive overload determining the prevalence of osteoclastic bone resorption phenomenon in bone remodeling.…”
Section: Discussionmentioning
confidence: 86%